2021
DOI: 10.1186/s40902-021-00322-6
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 on the injury pattern for maxillofacial fracture in Daegu city, South Korea

Abstract: Background This study aimed to analyze the impact of COVID-19 on oral and maxillofacial fracture in Daegu by comparing the demographic data in 2019 and 2020, retrospectively. We collected data from all patients having trauma who visited the emergency room for oral and maxillofacial fractures. Methods This retrospective study was based on chart review of patients who visited the emergency department of Kyungpook National University Hospital in Daegu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 25 publications
6
26
0
Order By: Relevance
“…These last measures have not only affected Italy but most of the nations in the world. As a consequence of this management, an important decrease in maxillofacial trauma in terms of incidence has been widely reported and described in international literature 1–5 . Moreover, elective surgery, and with it also maxillofacial one, has been gradually reduced nationwide in order to keep services operational without putting both healthcare professionals and patients at risk despite the assistance activity relating to traumatology and oncology has been guaranteed 6–8 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These last measures have not only affected Italy but most of the nations in the world. As a consequence of this management, an important decrease in maxillofacial trauma in terms of incidence has been widely reported and described in international literature 1–5 . Moreover, elective surgery, and with it also maxillofacial one, has been gradually reduced nationwide in order to keep services operational without putting both healthcare professionals and patients at risk despite the assistance activity relating to traumatology and oncology has been guaranteed 6–8 .…”
mentioning
confidence: 99%
“…As a consequence of this management, an important decrease in maxillofacial trauma in terms of incidence has been widely reported and described in international literature. [1][2][3][4][5] Moreover, elective surgery, and with it also maxillofacial one, has been gradually reduced nationwide in order to keep services operational without putting both healthcare professionals and patients at risk despite the assistance activity relating to traumatology and oncology has been guaranteed. [6][7][8] The purpose of this retrospective study is to analyze the management of maxillofacial trauma during the COVID-19 pandemic period at ''San Salvatore Hospital'' of L'Aquila and compare results with two different two-year periods, respectively, 2015-2016; 2017-2018 focusing our attention on incidence, age, gender, and etiology.…”
mentioning
confidence: 99%
“…Following lockdown regulations we observed a significant decline in maxillofacial fractures up to 49% compared to the same period in 2018, 2019 and 2021. Other studies found a decline in maxillofacial fractures as well [ [14] , [15] , [16] ]. The overall reduction of maxillofacial fractures could be attributed to the decrease in traffic-related injuries, as numbers of other mechanisms of trauma remained approximately the same.…”
Section: Discussionmentioning
confidence: 94%
“…COVID‐19 related restrictions have altered the epidemiology and aetiology of trauma. Some reports suggest that while the total number of facial fractures have decreased in this period, especially fractures related to sport, the proportion of assaults have increased and the number of alcohol related facial fractures have increased significantly 29,30 . Interpersonal violence and IPV may have increased with increased alcohol consumption and COVID‐19 lockdowns 31–33 .…”
Section: Discussionmentioning
confidence: 99%
“…Some reports suggest that while the total number of facial fractures have decreased in this period, especially fractures related to sport, the proportion of assaults have increased and the number of alcohol related facial fractures have increased significantly. 29,30 Interpersonal violence and IPV may have increased with increased alcohol consumption and COVID-19 lockdowns. [31][32][33] Due to COVID-19 restrictive measures, alcohol consumption in the home has increased, which is where the majority of the assaults leading to women's facial fractures occur.…”
Section: Covid-19mentioning
confidence: 99%